1995
DOI: 10.1007/bf00192626
|View full text |Cite
|
Sign up to set email alerts
|

Pattern recognition in honeybees: eidetic imagery and orientation discrimination

Abstract: The roles of eidetic imagery and orientational cues, respectively, in the discrimination of visual patterns by honeybees (Apis mellifera) were evaluated by training the bees to discriminate between patterns consisting of periodic, black and white square wave gratings. Training and tests with a number of different pairs of patterns revealed that bees use orientational cues almost exclusively, if such are present, and make use of eidetic images only when orientational cues are not available. On the other hand, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Several previous studies have considered the possibility that honeybee spatial vision is mediated either by retinotopic (Giger and Srinivasan, 1995;Gould, 1985;Wehner, 1967;Wehner, 1981), configural mechanisms (Avarguès-Weber et al, 2011;Avarguès-Weber et al, 2010c) and/or a combination of multiple mechanisms Efler and Ronacher, 2000). Experiment 1 is consistent with a retinotopic mechanism as once the bees had learned the task they were not able to transfer the learned rule to novel stimuli; specifically there appears to have been a requirement that the stimulus elements should have a fixed relationship to what was learned for correct decisions to be made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous studies have considered the possibility that honeybee spatial vision is mediated either by retinotopic (Giger and Srinivasan, 1995;Gould, 1985;Wehner, 1967;Wehner, 1981), configural mechanisms (Avarguès-Weber et al, 2011;Avarguès-Weber et al, 2010c) and/or a combination of multiple mechanisms Efler and Ronacher, 2000). Experiment 1 is consistent with a retinotopic mechanism as once the bees had learned the task they were not able to transfer the learned rule to novel stimuli; specifically there appears to have been a requirement that the stimulus elements should have a fixed relationship to what was learned for correct decisions to be made.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have discussed the possibility of multiple systems potentially underlying some of the discrepancies observed in different experiments Efler and Ronacher, 2000;Giger and Srinivasan, 1995). Although clear evidence of the use of multiple mechanisms remains outstanding, with many papers favouring one strategy over another, here we investigate if there is evidence of multiple strategies that can be used based on the experimental methodology.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In another insect model, Drosophila, it has recently been shown that experience with visual stimuli improves feature extraction from complex visual stimuli, and that the mushroom body region of the brain is critical in shape feature extraction (Peng et al, 2007). Two possible mechanisms by which insects might recognise visual stimuli include a retinotopictemplate strategy and/or the use of specific features extracted from a scene (Efler and Ronacher, 2000;Giger and Srinivasan, 1995;Horridge, 2005;Stach et al, 2004;Stach and Giurfa, 2005). In Drosophila (Dill et al, 1993;Peng et al, 2007) and ants (Cartwright and Collett, 1983;Graham et al, 2007) there is evidence that these insects use a retinotopic-template strategy, and in bees there is evidence that individuals use feature extraction, which may develop into configural type processing with experience (Stach et al, 2004;Stach and Giurfa, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…von Frisch, 1914;Baumgärtner, 1928;Hertz, 1929a;Hertz, 1929b;Hertz, 1931;Hertz, 1933;Hertz, 1935;Schnetter, 1968;Wehner, 1969;Cruse, 1972;Anderson, 1977;Srinivasan and Lehrer, 1988;Collett and Cartwright, 1983;Menzel and Lieke, 1983;Giger and Srinivasan, 1995;Giurfa et al, 1996a;Efler and Ronacher, 2000;Stach et al, 2004;Zhang et al, 2004;Dyer et al, 2005) (for reviews, see Wehner, 1972;Wehner, 1981). The early attempts were devoted to discover which particular features such as pattern border length, density, edge orientation or degree of disruptiveness could be discriminated by bees.…”
Section: Introductionmentioning
confidence: 99%